Students' perspectives of a hybrid learning system in Kazakhstani higher education: A case study - Amirova, Amina; Zhumabayeva, Aziya; Zhunusbekova, Aziza; Arenova, Assyl; Nygymanova, Nurbanu (Journal of Education and e-Learning Research, 2024)
Hybrid learning is a relatively new approach in Kazakhstan's educational system. The transition to a new format necessitates a significant amount of effort and restructuring at the universities. The problems of researching the advantages and disadvantages of implementing this kind of instruction in the classroom are very relevant. The study's goal was to investigate students' attitudes towards implementing a hybrid learning environment. A qualitative method of data analysis was applied in the study. 1,186 students participated in hybrid learning at various universities in Kazakhstan. According to the findings, students value the flexibility and convenience of attending classes remotely through a two-way video conference. However, the findings also indicate that this new learning environment faces several pedagogical and technological challenges. These findings emphasize the importance of assisting students in understanding hybrid learning resources and goals thereby creating opportunities for success in hybrid learning. Policymakers in education can use it as a guide to develop policies related to crisis management or inclusive education as well as curriculum documents and resources for hybrid learning.